Dampak Sinergi Kepemimpinan dan Loyalitas terhadap Peningkatan Kinerja Karyawan : Studi Kasus Usaha Percetakan Kebayoran Lama - Della Adelia; Nuraeni Nuraeni (Perhimpunan Sarjana Ekonomi dan Bisnis, 2026)
The research is motivated by the growing importance of human resource management in MSMEs, particularly in competitive service sectors such as digital printing, where employee performance plays a critical role in business sustainability and service quality. This study aims to analyze the influence of leadership and employee loyalty on employee performance in digital printing micro, small, and medium enterprises (MSMEs) located in Kebayoran Lama, Jakarta Selatan. A quantitative approach with a survey method was employed. Data were collected through questionnaires distributed to 97 employees and analyzed using multiple linear regression. The results indicate that leadership does not have a significant effect on employee performance, while employee loyalty shows a positive direction of relationship but is not statistically significant. The coefficient of determination reveals that leadership and employee loyalty jointly provide a limited contribution in explaining variations in employee performance. These findings suggest that employee performance in digital printing MSMEs is influenced by various internal organizational factors beyond leadership and employee loyalty. Therefore, a more comprehensive and contextual human resource management approach is required to improve employee performance in digital printing MSMEs.